PRODUCTIVE AND MARKET ANALYSIS OF BETA-CAROTENE OBTAINED FROM THE MICROALGA DUNALIELLA SP.: CURRENT SCENARIOS AND FUTURE PERSPECTIVES - Viana, Natália Moreno; Da Silva Júnior, Jaim José; Bueno, Guilherme Wolff [UNESP]; Machado, Levi Pompermayer [UNESP]; Ferreira, Maria Fernanda Nince; Trombeta, Thiago Dias (RGSA- Revista de Gestao Social e Ambiental, 2024)
Purpose: Present the carotenoid market with a focus on beta-carotene extracted from Dunaliella sp., a microalga capable of synthesizing significant amounts of beta-carotene. Theoretical framework: Beta-carotene is a natural pigment with applications in the food industry, serving as a precursor to vitamin A and playing a role in preventing various diseases. Microalgae of the genus Dunaliella sp. produce larger quantities of beta-carotene compared to other natural sources; however, their cultivation cost limits their competitiveness. Method: A quali-quantitative approach was employed to synthesize data from scientific literature, reports, and market databases. A patentometric search was conducted in the Derwent Innovation Index (DII) database, where 213 patent citations were identified. Results and conclusion: The global beta-carotene market is growing; however, Brazil has low participation and is dependent on imports. The demand for Dunaliella sp. for beta-carotene extraction is also increasing; however, its production cost is not competitive. Patents indicate an interest in optimizing cultivation methods and genetically improving microalgae strains to make production viable. Implications of the research: The study aims to contribute to a better understanding of the potential of beta-carotene obtained from Dunaliella sp. and its market scenario, as well as to highlight production bottlenecks and the potential for Brazil's integration into this market. Originality/value: The biomass production of Dunaliella sp. presents environmental advantages compared to the cultivation of terrestrial crops, such as the non-use of arable land for food production, along with the potential for effluent bioremediation as an environmentally friendly cultivation process, aligning with various UN-SDGs.
ANÁLISE PRODUTIVA E MERCADOLÓGICA DE BETACAROTENO OBTIDO DA MICROALGA DUNALIELLA SP.: CENÁRIOS ATUAIS E PERSPECTIVAS FUTURAS
Keywords: Beta-Carotene; Bioeconomy; Carotenoids; Dunaliella SP; Market; Microalgae